Integrating the TPACK Model in Teaching Mahārah al-Qirāʾah: An Educational Innovation Based on Technology - syukran syukran; samsul ulum; umi machmudah; Burhan Yusuf Habibi; Achmad Ja'far Sodik (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2025)
This study aimed to identify the concrete form of integrating the TPACK model in teaching reading skills (Mahārah al-Qirāʾah) to Arabic Language Education students at IAIN Lhokseumawe. Using a descriptive qualitative approach, data were collected through observations and interviews with the head of the study program, 2 lecturers, and 8 students. The data were analyzed through simplification, presentation, and conclusion drawing. The findings showed that the integration of the TPACK model in Mahārah al-Qirāʾah was carried out through three main stages: planning, implementation, and evaluation. Lecturers applied interactive and collaborative methods that enhanced students’ Arabic reading skills, including comprehension, fluency, and digital literacy. These efforts led to increased student engagement and motivation in learning. Therefore, the study concludes that the integration of TPACK in teaching Qira'ah was effectively implemented and aligns with the aim of providing an alternative model to improve reading skills in the Arabic Language Education Study Program at IAIN Lhokseumawe.